Rapid non-destructive sizing of microstructural surface integrity features using x-ray diffraction. (October 2022) - Brown, Matthew; Crawforth, Pete; Curtis, David
Abstract: In this study, rapid non-destructive sizing of machining-induced subsurface white layers and plastic deformation is achieved through x-ray diffraction peak breadth measurements. Sizing to within 0.5–2 μm is shown to be possible for features thinner than the x-ray penetration depth with inspection times under 1 min achievable. Whilst the technique can detect features larger than the penetration depth, accurate sizing is not possible. Appropriate selection of different x-ray radiation and diffraction peaks can be used to increase or decrease the penetration depth to improve sizing accuracy at larger and thinner feature thicknesses, respectively. However, there is a depth limit for each material imposed by the smallest wavelength of radiation that can be used and the highest angle diffraction peak that can be resolved. The dependence of peak breadth on deformation or white layer thickness can be modelled by assuming a linear or exponential decay in strain across the feature thickness.